'There was no real information about China in South Africa': revisiting the history of the establishment of diplomatic relations between South Africa and China (1950s–1990s). Issue 3 (3rd July 2019) - Jiang, Lu; Shu, Zhan
ABSTRACT: The establishment of diplomatic relations between South Africa and China is an under-researched topic. Even less examined is the role of party-to-party relations between the African National Congress (ANC) and the Communist Party of China (CPC) in the process of building relations between these two states, as well as that of the early contact between South Africa's National Party (NP) government and China. This research finds that the expectations of Pretoria and Beijing were largely incompatible in the early 1990s while no fundamental disagreement existed between South Africa and Taiwan at the time. The 'Mandela factor' and the general lack of knowledge about China in South Africa, furthermore, contributed to the prolonged process of building formal relations. In addition, the article also argues that the legacies of the early inter-party relations between the ANC and CPC, which played a role in South Africa's decision-making and opinion formation in the early 1990s, cannot be ignored, and helps to explain the delay in the establishment of diplomatic relations to 1998.